Резонансні перенапруги у несинусоїдному режимі магістральної електричної мережі - Кузнецов, В.Г; Тугай, Ю.І.; Кучанський, В.В.; Лиховид, Ю.Г.; Мельничук, В.А. (Електротехніка і електромеханіка, 2018)
Резонансні перенапруги в магістральних електричних мережах виникають внаслідок випадкового збігу параметрів
схеми та режиму і можуть існувати порівняно тривалий час. Тому традиційні засоби для обмеження короткочасних
комутаційних перенапруг в даному випадку не є ефективними. Метою статті є дослідження перенапруг, що виникають у магістральних електричних мережах на вищих гармонійних складових. Для цього використовувалися імітаційне та математичне моделювання в середовищі MATLAB&Simulink . Показано, що несинусоїдальні спотворення виникають при ввімкненні лінії електропередачі на невантажений автотрансформатор. Визначені частоти, при яких
виникають перенапруги на вищих гармонійних складових. Запропоновано використання пристрою керованої комутації для запобігання перенапругам даного класу і розроблена модель для визначення відповідних налаштувань. Резонансные перенапряжения в магистральных электрических сетях возникают вследствие случайного совпадения
параметров схемы и режима и могут существовать сравнительно длительное время. Поэтому традиционные средства для их ограничения в данном случае неэффективны. Целью статьи является исследование перенапряжений,
возникающих в магистральных электрических сетях на высших гармониках. Для этого было использовано имитационное и математическое моделирование в среде MATLAB&Simulink. Показано, что несинусоидальные искажения возникают при включении линии электропередачи на автотрансформатор в режиме холостого хода. Определены соответствующие частоты. Предложено использование устройства управляемой коммутации для предотвращения перенапряжения данного класса и разработана модель для определения соответствующих настроек. Purpose. The resonant overvoltage arises in main electrical networks as a result of random coincidence of some parameters of
circuit and its mode and it may exist for a relatively long time.
Therefore, the traditional means of limitation of short duration
commutation surges are not effective in this case. The study determines conditions of appearance and development of non-sinusoidal
mode after switching idle autotransformer to the overhead line of
extra high voltage. The purpose of the paper is to choice measures
for prevention overvoltage, too. Methodology. The study has used
the result of extra high voltage line testing, the methods of electric
circuit theory and the simulation in the MATLAB & Simulink package. Results. The simulation model of the extra high voltage transmission line for the study of resonant non-sinusoidal overvoltage is
developed. The conditions for the appearance of resonant circuits in
the real power line are found and harmonic frequency in which
overvoltage arises are obtained. The study proposes using the controlled switching device as a measure to prevent resonance surges
and determines the appropriate settings. Originality. The expression
for calculation of resonant length of extra high voltage line was
derived. The special investigation of processes in the resonant circuit of the extra high voltage transmission line for higher harmonic
components of voltage is carried out. The program of switching for
control apparatus that prevents non-sinusoidal overvoltage has
been developed at the first time. Practical value. The using of the
proposed settings of controlled switchgear will prevent the occurrence of hazardous resonant surge on higher harmonic components
of voltage.